Исследование конструктивных параметров системы ротационных эндодонтических инструментов (LLC "Endo Press", 2020)
Design features of the endodontic instrument determine its essential properties. Information about these design features carries inference about instrument properties and makes possible a comparative analysis of instruments with different design. The aim of the present work is a quantitative study and analysis of the FlexMaster instruments design features. Thirty instruments of different size and taper have been included in this study. SEM examination of all instruments and their cross-sections was made to determine the following design parameters: tip angle, fluting angle, pitch length, fluting depth, internal and external diameters and the angles of cutting blade. Design features analysis of the FlexMaster instruments allows pointing out its outstanding characteristics: 1) good cutting efficiency; 2) high torsional resistance; 3) low flexibility; 4) aggressive tip; 5) low controllability of cutting process due to substantial self-feeding effect.